Penerapan Model Project Based Learning untuk Meningkatkan Motivasi Belajar PAI di SMA - Nurwidya Putri; Jamaluddin Jamaluddin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Many problems during the learning process result in a decrease in student learning motivation which has a negative impact on academic achievement and makes students less active. This can be seen from (1) the rarity of students asking or responding to questions (2) students rarely communicate difficulties to teachers (3) students are also often late in submitting assignments. With these problems, researchers tried to apply the project based learning model with a constructivist approach analysis implemented at SMA Negeri 1 Majene. The subjects of this study were 38 grade X MIPA students of PAI subjects and one of the PAI subject teachers. The method used is descriptive qualitative, data collection techniques are observation, interviews and documentation. Data analysis techniques by means of data collection, data reduction, data presentation and drawing conclusions. The results of this study students have been faced with a problem and have the ability to analyze complex problems, investigate, evaluate, viewpoints and draw conclusions based on evidence and reasoning coupled with the spirit of student collaboration is very compact in each group, where a collaboration is a process of achieving a goal that is done together helping each other, and the most supportive thing in the learning process activities is the extrinsic factor of students which is the stimulation from outside, namely the people around them. In the application of constructivism in learning, it is expected that students are more active and teachers as facilitators become more innovative.